INCREASING STUDENT’S SPEAKING ABILITY USING PROCEDURE TEXT THROUGH LIVE PERFORMANCE IN THE SECOND GRADE AT SMK BHAKTI LUHUR MALANG - Mikhael Beka (Graduate Program, University of Islam Malang, 2020)
AbstractThe students of SMK-Bhakti Luhur Malang hadlow achievement in English atspeaking ability. They didn’t have strong motivation in studying English, they were afraidto speak English. Therefore, a special method is needed to improve the students‘speaking ability. The research design of this study was a classroom action research. Thesubjects of the research were 30 students. This study was done in two cycles. Howeverbefore implementing these cycles, the researcher carried out preliminary study to findout the students’ problem in studying English.In this class action research aims to improve the teaching and learning processof English to measure their improvements in speaking ability, the researcher hasdetermined the criteria of success. And the student was said successful if student got aleast 70. The class percentage was said successful if 85% the students or more reachedthe passing grade. The researcher employed the collaborative classroom action researchdesign and the researcher was assisted by a collaborator teacher in conducting thestudy. The research was conducted in three main steps; Planning of action, observation,and reflection. The objective of this study is to improve the speaking ability in proceduretext live performance of the second grade at SMK – Bhakti Luhur Malang. This researchuse Classroom Action Research adapted from Stephan Kemmis and Robin Mc.Taggart(1992 in Arikuntoro 2002 ) in planning, action, observing, and reflecting on the datacollected from teaching and learning process and the students speaking presentationtest. The subjects of this students were 30 students the second grade. This research oftwo cycles because in the second cycle the criteria success achieved. Each of themconsisted of three meetings for teaching learning process. The data were collectedthrough : observation sheet and presentation test. In this research, the researcher usedkinds of procedure text live performanceThe finddings indicated that using procedure text live performance is one of thestrategy-improved students ability in speaking procedure text . After the researcherconducted the first and second cycle, it was shown that the result of the second cycleimproved. Only 5 of 30 students (15%) still received scores under the target 70. Theimprovement of the students score had met the criteria of success, because twenty fivestudents(85%) achieved the target score (70). Therefore, it is suggeted to Englishteachers and future researchers who want to improve the students English speakingability in procedure text live performance.it also makes the students more interested and active in teaching and learning process.Key Words: Increasing, Live performance, Speaking Skill.